Association between nutrient patterns and bone mineral density among ageing adults. (December 2017) - Melaku, Yohannes Adama; Gill, Tiffany K.; Taylor, Anne W.; Adams, Robert; Shi, Zumin
Summary: Background and aim: There is limited evidence on the link between the overall nutrients intake from diet and bone mineral density (BMD). We assessed the association between nutrient patterns and BMD among an ageing Australian population. Methods: Participants (n = 1135; males, 45.8%; median age, 62.0 years) with dietary and BMD data in the North West Adelaide Health Study (NWAHS) were included. Dietary intake was assessed using a food frequency questionnaire. BMD was measured using dual-energy X-ray absorptiometry. Nutrient patterns were identified by factor analysis. Linear regression analyses were conducted to assess the association between nutrient patterns and BMD (mg/cm 2 ). Multiple imputation and sensitivity analyses were conducted to investigate the effect of missing data on the estimates. Results: Three nutrient patterns (mixed-source [potassium, calcium, fibre, retinol and Vitamin B12 ], animal-sourced [cholesterol, protein, Vitamin B12 and fat] and plant-sourced [fibre, carotene, vitamin C and Lutein]) were identified. After adjusting for socio-demographic, lifestyle and behavioural characteristics, chronic conditions and energy intake, animal (β = −4.07; 95% confidence interval (CI): −11.89, 3.76) and plant-sourced (β = −0.99; 95% CI: −7.43, 5.45) patterns were not associated with BMD. However, we found that the mixed-source pattern was positively associated with BMD (β = 10.86; 95% CI: 1.91, 19.80). We did not find interactions between the pattern, other covariates and BMD. The multiple imputation and sensitivity analyses including missing data identified similar patterns of association between nutrient patterns and BMD. Conclusions: Whereas animal- and plant-sourced nutrient patterns are not associated with BMD, mixed-source pattern may have benefit in prevention of reduced BMD.